Design, Development, and Performance Evaluation of an Augmented Reality-Based Hybrid Pop-Up Media System for Elementary Ecosystem Learning - Moch Bayu Ibrahim S; Suwito Eko Pramono; Fakhruddin Fakhruddin; Bambang Subali (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study aimed to develop an augmented reality based ecosystem pop-up book for elementary science learning and to evaluate its validity and practicality as a hybrid instructional medium integrating physical pop-up structures with digital augmented reality visualization. Methodology: This study employed a Research and Development approach using the 4D model: Define, Design, Develop, and Disseminate. The augmented reality based media were developed using Unity 3D and Vuforia Software Development Kit (SDK) with marker-based tracking. The development process involved needs analysis, expert validation, revision, and practicality testing involving 139 fifth-grade students, five media experts, and five subject matter experts. Data were analyzed using percentage scores, mean scores, standard deviation, and Aiken’s V coefficients. Main Findings: The developed media achieved a validity score of 92.6% from media experts (M = 4.63; Aiken’s V = 0.89) and 92.2% from subject matter experts (M = 4.61; Aiken’s V = 0.90), both categorized as very valid. The practicality test obtained 95.67% (M = 4.78), categorized as very practical. The AR system also demonstrated stable technical performance with marker detection accuracy of 96.4%, tracking stability of 93.8%, response time of 428 ms, rendering performance of 29–32 fps, and an SUS score of 87.2. Novelty/Originality of this study: This study introduces a hybrid instructional medium integrating three-dimensional pop-up book structures with augmented reality technology in ecosystem learning for elementary education, providing combined tactile and digital learning experiences through a marker-based augmented reality visualization system optimized for classroom use.